(untitled) (SAARC Journal of Agriculture, 2022)
A study was conducted at Chanchra, Sadar Upazila, Jashore, Bangladesh during Rabi seasons of 2019-20 and 2020-21 to evaluate pre-harvest treatments of inorganic nutrient sources on yield and shelf life of broccoli through Randomized Complete Block Design (RCBD) with three replications and six treatments which were; T1= soil test based 50% NPK with blanket dose, T2=soil test based 75% NPK with blanket dose, T3= soil test based 100% NPK with blanket dose, T4=soil test based 125% NPK with blanket dose, T5=local farmers practice (N138 P75 K94 S27 Zn5 kg ha-1),T6 = control.Completely Randomized Design (CRD) was designed to determine the shelf life of broccoli with three replications considering three factors; (i) pre-harvest treatments of inorganic sources of nutrient; (ii) storage materials at room temperature and (iii) storage materials at cold storage condition.Findings revealed that the effects of different inorganic sources of nutrients significantly influenced on yield and shelf life of broccoli. The treatment T3 (soil test based 100% NPK with blanket dose) resulted in better marketable curd yield with maximum gross returns, net returns and Benefit Cost Ratio(BCR) as compared to other treatments. The treatment T1 (soil test based 50% dose of NPK with blanket dose) recorded the maximum shelf life of 6.57 daysand 6.83 days at room temperature (14-240C with RH 60-65%) and 23.65 days and 24.25 days at cold storage (40C with RH 90-95%) condition using High -Density Polyethylene (HDP;15 micron) vacuum pack during the years of 2019-20 and 2020-21 respectively. SAARC J. Agric., 20(1): 131-141 (2022)